Gold conjugated-magnetite nanoparticles for magnetic concentration towards reproducibility and repeatability of SERS measurements - Miyazaki, Celina M. [UNESP]; Martin, Cibely S. [UNESP]; Constantino, Carlos J.L. [UNESP] (Elsevier, 2023)
Variables such as uncontrolled colloid aggregation, and even the natural motion of particles named Brownian motion, lead to small variations in the molecular position and arrangement between molecule and nanoparticles, thus influencing SERS magnitude. To address this issue, we synthesized gold conjugated-magnetic nanoparticles (AuMNP) as a SERS platform for dopamine (DA) detection. Unlike conventional colloids such as silver and gold, which are unable to provide SERS for DA, the AuMNP not only yielded SERS signal but also improved repeatability and reproducibility. Under a magnetic concentration using a neodymium magnet, the standard deviation of ten measurements was found to be 19.4 versus 800 (arb.un.) for the magnetically concentrated and dispersion measurements, respectively. The hot spots formation in the AuMNP and the possible DA − AuMNP interactions are in the origin of the obtained SERS signal. Additionally, the DA SERS signal varied with concentration according to the Freundlich isotherm model, indicating multilayer adsorption. The limit of detection was in order of 10–6 mol/L without further optimizations.
Keywords: Dopamine; Gold conjugated-magnetic nanoparticles; Magnetic concentration; SERS